Age-Related Macular Degeneration Models Induced by Polyethylene Glycol (PEG) - Reece Mitchell; Connor Logan; Valeriy V. Lyzogubov; Nalini S. Bora; Puran S. Bora (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Age-related macular degeneration (AMD) is a leading cause of irreversible blindness worldwide. Polyethylene glycol (PEG) can activate the alternative pathway of the complement system and induce choroidal neovascularization (CNV) in mice, has been recently reported. Currently, no other investigator has demonstrated CNV after PEG injection in the mouse eye. AMD pathogenesis in mice through subretinal PEG treatment of RPE cells and retinal layers. Male C57BL/6 mice were injected (subretinal) with 2 \(μ\)L of solution containing 0.5 mg and 1.0 mg of PEG or PBS in control groups. Eyes were harvested on days 1, 3, and 5 after injection and processed for analysis. Sections were immunohistochemically stained for complement component C3, membrane attack complex (MAC), and cytokeratin 18. Light and laser confocal microscopy was used for image capturing. PEG increased deposition of C3 and MAC on RPE cells and on all retinal layers after 1.0 mg injection. PEG induced loss of cellular contacts between RPE cells and migration of RPE cells in the subretinal space at day 1 after PEG injection. After 0.5 mg PEG injection, increased size of RPE cells was detected at days 3 and 5. Apoptotic bodies were observed in an outer nuclear layer at days 3 and 5 after 0.5 mg PEG treatment. RPE cells with dark cytoplasm and condensed chromatin were observed. Higher doses of PEG induce CNV, encourage RPE cell proliferation and death, and damage photoreceptors in mice. This simple and fast model may be useful to explore the pathogenesis of both dry and wet AMD.